The Exploring the relationship between stress, sleep quality, mobile phone usage and physical activity among physiotherapy students: a survey study - Singh, Arshpreet; Singh, Pankajpreet; Bindra, Supreet; Mansoori, Shavez (International Journal of Research in Medical Sciences, 2026)
Background: Physiotherapy students are frequently exposed to academic, clinical, and personal stressors that may affect their sleep quality, smartphone usage patterns, and physical activity levels. The aim of the study is to explore the relationship between stress, sleep quality, smartphone addiction, and physical activity among physiotherapy students. Methods: A cross-sectional correlational study was conducted among 300 physiotherapy BPT and MPT students. Data were collected using the SSI, PSQI, SAS-SV and IPAQ-SF. Descriptive statistics were used to summarize participant characteristics and study variables. Since the data were non-normally distributed, Spearman’s rank correlation test was used to examine associations among variables. Results: Among 300 participants, 203 (67.7%) were female and 97 (32.3%) were male, most were aged 21–25 years. Mild to moderate smartphone addiction was common, 55.3% showing mild and 40.3% moderate addiction. Nearly half of the students reported moderate stress (48.0%), moderate sleep disturbances (48.0%), while low physical activity was observed in 72.0%. Smartphone addiction showed a significant positive correlation with poor sleep quality (r=0.191, p=0.001), whereas physical activity was negatively correlated with sleep disturbances (r=−0.162, p=0.005). No significant associations were found between stress, smartphone addiction, physical activity, and sleep quality. Conclusions: Smartphone addiction, poor sleep quality, moderate stress, and low physical activity were common among physiotherapy students. Higher smartphone addiction was associated with poorer sleep, while greater physical activity was linked to better sleep quality. Encouraging healthier smartphone habits and regular physical activity may support students' sleep and overall well-being.